Peran Energi Terbarukan dan Energi Nuklir: Analisis Empiris Environmental Kuznets Curve di Negara BRICS Periode 1996-2016 - Mega Dwi Cahyani; Jaka Aminata (Universitas Diponegoro, 2020)
This study aims to analyze the impact of per capita gross domestic product (GDP), per capita non-renewable energy consumption, per capita renewable energy consumption, and per capita nuclear energy consumption within the framework of the environmental Kuznets curve (EKC) for the case of BRICS. This study used panel data, consist of 5 countries and 21 periods (1996 to 2016). Secondary data from World Bank and British Petroleum Energy are used. Fixed Effect Model are used to measure the impact of per capita gross domestic product (GDP), per capita non-renewable energy consumption, per capita renewable energy consumption, and per capita nuclear energy on carbon dioxide emissions in BRICS. This study results indicate that non-renewable energy consumption have significant impact on increasing BRICS’S carbon dioxide emissions in both short and long run. Renewable energy consumption and nuclear energy consumption have significant impact on reducing BRICS’S carbon dioxide emissions in long run. The empirical result also indicate that Environmental Kuznets Curve (EKC) is proven in BRICS by forming an inverted-U curve. Turning point in BRICS occurred in 2016 when GDP per capita was 2.084.677.